Working under Pressure: Scleroderma Presenting with Bilateral Exudative Retinal Detachment in the Context of Scleroderma Renal Crisis: A Case Report - Rem Aziz; Cody Lo; James T. Denstedt; Bernard Hurley (Case Reports in Ophthalmology, 2024)
This is an observational case report to detail a novel case of scleroderma renal crisis presenting as bilateral exudative retinal detachments in a patient with newly diagnosed systemic sclerosis. An otherwise healthy 58-year-old female presented primarily with vision complaints and was found to have malignant hypertension (230/120 mm Hg) and bilateral exudative retinal detachment on dilated fundus examination and macular OCT scan. Further history revealed sclerodactyly, mild dysphagia, and dyspnea. She was diagnosed with diffuse systemic sclerosis and Sjogren’s syndrome complicated by an episode of scleroderma renal crisis based on initial medical workup. She was admitted to intensive care for management of refractory hypertension with IV antihypertensive therapy. Three months after treatment, her visual symptoms and ocular findings resolved. The presence of exudative retinal detachment among other signs of hypertensive retinopathy warrants thorough systemic screening for underlying causes of malignant hypertension, including systemic sclerosis. Treatment of the underlying disease with urgent antihypertensive therapy resolved the exudative retinal detachments and restored vision in the case of a scleroderma renal crisis.